Hectorite composite antibacterial antioxidant hydrogel as well as preparation method and application thereof
Lithostone composite antibacterial and antioxidant hydrogel was prepared by combining lithostone with zwitterionic monomer and loading of EGCG-Cu nanocomplex, which solved the mechanical properties and antibacterial stability of hydrogel dressings, and achieved the realization of the realization of the The continuous release and antibacterial effect in the wound promote wound healing.
Patent Information
- Application Number
- CN202411408890.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
Existing hydrogel dressings have insufficient mechanical properties, poor adhesion, and antibacterial stability and sustained release problems, making it difficult to continuously release antioxidants in wound tissue.
The lithium saponite is combined with zwitterionic monomer to prepare a double crosslinked hydrogel through crosslinking, and the EGCG-Cu nanocomplex is loaded into the hydrogel to form a lithium saponite composite antibacterial and antioxidant hydrogel. Improve its mechanical properties and antibacterial properties, while achieving sustained sustained release of EGCG and copper ions.
It improves the mechanical strength and adhesion of the hydrogel, enhances the antibacterial and antioxidant properties, ensures the stability and continuous release of the dressing, and promotes wound healing and antibacterial effects.
Smart Images

Figure CN119236159A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a laponite composite antibacterial and antioxidant hydrogel and a preparation method and application thereof. Background Art
[0002] Wound dressings play an extremely important role in modern medicine. Their main functions are to keep wounds clean, prevent infection, promote healing and provide mechanical protection. The selection and design of dressings vary according to the type, size and healing stage of the wound. In addition to having good biocompatibility, breathability and moisturizing functions, ideal wound coverings should also have certain antibacterial functions to avoid external microbial contamination, while simulating the mechanical properties of the skin to reduce discomfort during replacement.
[0003] In recent years, hydrogel dressings have attracted widespread attention due to their high water content, biocompatibility and moisturizing function. Researchers are committed to giving hydrogels more functionality by means of modification, compounding or loading drugs, such as self-healing hydrogels, degradable hydrogels, antibacterial hydrogels, antioxidant hydrogels, drug delivery hydrogels and smart hydrogels. However, existing hydrogel dressings still face some problems: although natural polymer materials such as sodium alginate and chitosan have good biocompatibility and antibacterial properties, they have poor stability and low mechanical strength; synthetic polymer materials such as polyurethane and polyethylene glycol are low-cost and easy to produce, but lack biocompatibility, and unreacted monomers may even cause further damage to the wound.
[0004] Although zwitterionic hydrogels exhibit excellent water content, biocompatibility and anti-fouling properties due to their unique chemical structure, in addition, the quaternary ammonium functional groups and sulfonic acid functional groups in zwitterions have strong dipole moments, which can form strong dipole interactions with carboxyl and amino groups in the skin or other human tissues to achieve adhesion of hydrogels to tissues. However, the poor mechanical properties caused by its high water content limit its performance in practical applications. In order to improve this situation, researchers have tried to prepare double network hydrogels by copolymerizing with other non-zwitterionic monomers or compounding with other hydrogel networks to improve their mechanical properties. Laponite, as a synthetic nanoclay, exhibits unique dual charge properties, with a negative charge on the surface and a positive charge on the edge. In the dispersed state, the interaction between particles is mainly manifested as electrostatic repulsion, which enables laponite to effectively combine with other ions to promote a stable colloidal system. Hectorite's excellent thixotropy, antibacterial properties, dispersibility, suspension and thickening properties, as well as adsorption and ion exchange properties, make it often used as an additive for polymers to improve the performance of polymers, and it has many applications in wound dressings, drug carrier delivery and other fields.
[0005] In addition, in the preparation of antibacterial dressings, copper ions, as an effective antibacterial agent, are used in hydrogels but are plagued by toxicity issues at high concentrations. High concentrations of copper ions may cause cell membrane damage and trigger intracellular oxidative stress, thereby damaging DNA, proteins, and lipids, and ultimately leading to cell death. In addition, excessive copper ions can also affect the proliferation and migration of fibroblasts, interfere with the synthesis of normal collagen, and are not conducive to wound healing. Epigallocatechin gallate (EGCG), as the main active ingredient in green tea, is a potent bioactive polyphenol compound with strong antioxidant and free radical scavenging effects. It can neutralize free radicals, reduce cell oxidative damage, and help prevent a variety of diseases and aging processes.
[0006] However, it is easy to undergo oxidation or polymerization under air, light and high temperature conditions, affecting its stability and bioavailability. Although studies have shown that loading EGCG into hydrogels can improve its stability, how to control its sustained release in wound tissues remains a difficult problem. Summary of the invention
[0007] Purpose of the invention: The technical problem to be solved by the present invention is to provide a hydrogel that can solve the problems of insufficient mechanical properties and insufficient adhesion, achieve effective sustained release of antibacterial agents and have dual antibacterial and antioxidant properties in response to the deficiencies of the prior art.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a hectorite composite antibacterial and antioxidant hydrogel comprises the following steps: (1) Preparation of zwitterionic monomer-hectorite composite Laponite is dispersed in deionized water to obtain a dispersion, and a zwitterionic monomer is added and adsorbed on the surface of the Laponite through interionic interaction to obtain a zwitterionic monomer-Laponite complex.
[0009] (2) Preparation of double-crosslinked lithium soapstone composite hydrogel A zwitterionic monomer-lithium laponite complex, a main monomer, a cross-linking agent, an initiator and a catalyst are added to water, and the precursor solution is fully stirred. After cross-linking and curing, a double-cross-linked lithium laponite composite hydrogel is obtained; wherein lithium laponite (Laponite) is used as a physical cross-linking agent, the zwitterionic monomer is adsorbed on the surface of the lithium laponite (Laponite) through interionic action for physical cross-linking, and the main monomer and the zwitterionic monomer are polymerized for chemical cross-linking to prepare a double-cross-linked lithium laponite composite hydrogel.
[0010] (3) Preparation of EGCG-Cu nanocomplex A functional polymer deionized water solution was prepared, an inorganic copper salt was added for ultrasonic dispersion, EGCG was added for reaction, the final product was separated by centrifugation, and the product was washed and freeze-dried to prepare an EGCG-Cu nanocomplex.
[0011] (4) Preparation of hectorite composite antibacterial and antioxidant hydrogel The double-crosslinked lithium soapstone composite hydrogel in step (2) is immersed in the deionized water solution of the EGCG-Cu nanocomplex prepared in step (3) to allow the hydrogel layer to fully swell, and then taken out and vacuum dried to obtain the hydrogel.
[0012] Specifically, in step (1), the zwitterionic monomer is any one of carboxylic acid betaine methyl methacrylate (CBMA), 2-methacryloyloxyethyl phosphorylcholine (MPC), polycarboxylic acid betaines, and methacryloylethyl sulfonobetaine (SBMA), preferably methacryloylethyl sulfonobetaine (SBMA); the hectorite is nanoclay sodium magnesium lithium silicate, and its mass percentage in the dispersion is 0.2~8%, preferably 1~4% by mass; the molar ratio of the nanoclay sodium magnesium lithium silicate to the zwitterionic monomer is 1:0.2~1:10, preferably 1:1~1:6.
[0013] Specifically, in step (2), the main monomer is acrylic acid (AA) or methacrylic acid (MAA); The crosslinking agent includes any one of (MBA), divinylbenzene (DVB), N,N-bis(acryloyl)cystamine (Bacy), ethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, and 2,2-dithiodiethanol diacrylate, and the preferred crosslinking agent is N,N-methylenebisacrylamide; The initiator is a thermal initiator, a peroxide initiator or an azo compound initiator; wherein the thermal initiator includes any one of azobisisopropionitrile, azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, and dibenzoyl peroxide (BPO), and the peroxide initiator includes any one of hydrogen peroxide, ammonium persulfate or potassium persulfate; The catalyst is tetramethylethylenediamine (TEMED).
[0014] Specifically, in step (2), the concentration of the main monomer in the precursor solution is 0.05-1 g / mL, preferably 0.1-0.5 g / mL; the mass of the zwitterionic monomer accounts for 1-40% of the mass of the main monomer, preferably 10-25%; the cross-linking agent accounts for 0.05-1% of the mass of the main monomer, preferably 0.1-0.3%; the initiator accounts for 0.05-2% of the mass of the main monomer, preferably 0.05-1%; the catalyst accounts for 0.05-2% of the mass of the main monomer, preferably 0.05-1%.
[0015] Specifically, in step (2), the precursor solution is filled between two layers of polytetrafluoroethylene (PTFE)-covered glass slides with a thickness of about 1 to 2 mm, and placed in a drying oven at 60 to 120° C. for cross-linking and curing for 30 to 240 minutes to obtain a double-cross-linked hectorite composite hydrogel.
[0016] Specifically, in step (3), the functional polymer is polyvinyl pyrrolidone (PVP), and the concentration of the prepared aqueous solution is 10-100 mg / mL, preferably 40-60 mg / mL; the inorganic copper salt is any one of CuCl2, Cu(NO3)2, and CuSO4, preferably CuCl2; the molar ratio of EGCG to the inorganic copper salt is between 1:1 and 1:3, and the mass of the functional polymer is between 50% and 200% of the total mass of EGCG and the inorganic copper salt.
[0017] Specifically, in step (3), the functional polymer, inorganic copper salt and EGCG are mixed and the pH value is adjusted to 7-8. After reacting for 1-6 hours, the final product is separated by centrifugation, washed three times with deionized water, and freeze-dried to obtain the EGCG-Cu nanocomplex.
[0018] Specifically, in step (4), the concentration of the prepared deionized water solution of EGCG-Cu nanocomplex is 0.1-2 mg / mL, preferably 0.2-1.0 mg / mL; the double-crosslinked hectorite composite hydrogel is immersed in the deionized water solution of EGCG-Cu nanocomplex for 6-24 hours, and then the residual mixed solution on the surface is taken out and rinsed.
[0019] Furthermore, the hectorite composite antibacterial and antioxidant hydrogel prepared by the above preparation method is also within the protection scope of the present invention.
[0020] Furthermore, the present invention also claims to protect the use of the above-mentioned hectorite composite antibacterial and antioxidant hydrogel in the preparation of wound dressings. Beneficial Effects
[0021] (1) In the present invention, hectorite is a nanoclay, and its unique dual charge property enables it to effectively combine with other ions to form a stable colloidal system. The present invention constructs a hydrogel with a double cross-linked structure by adding hectorite. This structure can effectively disperse the stress, thereby improving the overall mechanical strength, extending the service life of the dressing, and reducing the possibility of deformation or breakage during use. In addition, this dressing has a more ordered and uniform pore structure, which is not only conducive to moisture management, but also promotes wound healing and antibacterial effects. Reasonable pore structure helps cell growth and tissue regeneration, accelerating the wound healing process.
[0022] (2) The zwitterionic material selected in the present invention has a high degree of hydrophilicity and can adsorb and retain more water molecules near its surface, thereby increasing the water content of the hydrogel. At the same time, the hydrophilicity of its surface reduces the adsorption of proteins and enhances the anti-protein adhesion of the hydrogel. This increase in water content and anti-protein adhesion properties enables the dressing to maintain the stability and reliability of its performance and function in a complex biological environment, and is not easily invalidated due to changes in the external environment.
[0023] (3) In the present invention, the use of zwitterions enhances the adhesion of the dressing to the skin. The surface charge distribution structure of the zwitterionic polymer increases the charge attraction between the dressing and the skin surface, thereby improving the adhesion to the skin and ensuring that the dressing is not easy to fall off or shift during use.
[0024] (4) By loading EGCG and copper ions, the present invention endows the hydrogel dressing with antioxidant capacity and antibacterial properties. EGCG is a potent polyphenol antioxidant, while copper ions have antibacterial properties.
[0025] (5) The nanocomposite formed by EGCG and copper ions in the present invention not only improves the stability of both, but also achieves a sustained release of EGCG and copper ions. The nanocomposite formed by the combination of EGCG and copper ions has a large specific surface area and special surface properties, which can more effectively encapsulate and protect EGCG and copper ions, prevent them from being adversely affected or released early in the environment, thereby improving the stability of both, and achieving a sustained sustained release effect, prolonging the biological effect time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0027] Figure 1 This is the structural Fourier transform infrared spectrum of the double-crosslinked lithium laponite composite hydrogel in Example 1.
[0028] Figure 2 This is a scanning electron microscope (SEM) image of the double-crosslinked hectorite composite hydrogel of Example 1.
[0029] Figure 3 This is the SEM image of the double-crosslinked lithium soapstone composite hydrogel of Example 3.
[0030] Figure 4 This is the SEM image of the hectorite composite antibacterial and antioxidant hydrogel of Example 7.
[0031] Figure 5This is a schematic diagram of the wrist adhesion activity of the hectorite composite antibacterial and antioxidant hydrogel in Example 8.
[0032] Figure 6 Schematic diagram of the stretching, bending, compression and knotting of the double-crosslinked lithium soapstone nanocomposite hydrogel in Example 4.
[0033] Figure 7 The elongation at break and the fracture toughness of the double-crosslinked hectorite composite hydrogel with different Laponite dosages in Example 1, Example 2, Example 3 and Example 4 are shown.
[0034] Figure 8 This is the in vitro release curve of EGCG in the laponite composite antibacterial and antioxidant hydrogel at different pH values in Example 7.
[0035] Fig. 9 The sizes of the inhibition zones of Example 4, Comparative Example 2 and Example 7 are shown.
[0036] Fig.10 Figure 1 is a graph showing the antioxidant performance of the hydrogel. (a) is a UV spectrum of the hectorite composite antibacterial and antioxidant hydrogel of Example 7 placed in a DPPH solution, (b) is a graph showing the scavenging ratio of DPPH by Example 7 and Comparative Example 1, and (c) and (d) are photos of the solution before and after the hectorite composite antibacterial and antioxidant hydrogel of Example 7 scavenges DPPH free radicals. DETAILED DESCRIPTION
[0037] The present invention can be better understood with reference to the following examples.
[0038] Example 1: Preparation of double cross-linked lithium laponite composite hydrogel 1 0.05 g of Laponite and 5 ml of deionized water were accurately weighed and added to a beaker, and ultrasonic dispersion was performed uniformly. 0.3 g of monomer methacryloylethyl sulfobetaine (SBMA) was accurately weighed and added to a beaker, and ultrasonic dispersion was performed to prepare an SBMA-hectorite composite.
[0039] SBMA-hectorite complex, 1.5g of acrylic acid (AA), 0.003g of crosslinker N,N-methylenebisacrylamide (MBA) and 0.0126g of initiator potassium persulfate (KPS) were added to 5ml of water and ultrasonicated again to ensure that all components were completely dissolved. Subsequently, 5 microliters of catalyst tetramethylethylenediamine (TEMED) were quickly added, and after being fully stirred, the mixture was immediately filled between two layers of polytetrafluoroethylene (PTFE)-covered glass slides with a thickness of about 1.5 mm, and placed in a drying oven at 80°C for crosslinking and curing for 0.5 h to prepare a double-crosslinked hectorite nanocomposite hydrogel material.
[0040] Fourier transform infrared spectrometer (FT-IR) was used to characterize the structure of the hydrogel in Example 1. Figure 1 1082 cm −1 and 617 cm −1 The peaks at 1630 cm -1 The peak that appears, corresponding to the C=O bending deformation of -COOH, 1390 cm -1 and 1530 cm -1 Corresponding to the symmetric and asymmetric vibrations of -COO-. 1710 cm -1 The characteristic absorption peak at 3440 cm is attributed to the C=C stretching vibration. -1 The stretching vibration of -OH group proves the existence of hydrogen bond in the hydrogel. Therefore, it can be confirmed by infrared spectroscopy that the final synthesized hydrogel is composed of Laponite, PSBMA polymer and PAA.
[0041] The morphology was characterized by SEM. Figure 2 The figure shows a scanning electron microscope (SEM) image of the hydrogel of Example 1. It shows interconnected and evenly distributed honeycomb structural features, in which the pore sizes are mostly concentrated in the range of 20-100 µm, and the pore wall structure shows significant fineness.
[0042] Example 2: Preparation of double cross-linked lithium laponite composite hydrogel 2 0.10 g of Laponite and 5 ml of deionized water were accurately weighed and added to a beaker, and ultrasonic dispersion was performed uniformly. 0.3 g of monomer methacryloylethyl sulfobetaine (SBMA) was accurately weighed and added to a beaker, and ultrasonic dispersion was performed to prepare a SBMA-hectorite composite.
[0043] SBMA-hectorite complex, 1.5g of acrylic acid (AA), 0.003g of crosslinker N,N-methylenebisacrylamide (MBA) and 0.0126g of initiator potassium persulfate (KPS) were added to 5ml of water and ultrasonicated again to ensure that all components were completely dissolved. Subsequently, 5 microliters of catalyst tetramethylethylenediamine (TEMED) were quickly added, and after being fully stirred, the mixture was immediately filled between two layers of polytetrafluoroethylene (PTFE)-covered glass slides with a thickness of about 1.5 mm, and placed in a drying oven at 80°C for crosslinking and curing for 0.5 h, thereby preparing a double-crosslinked hectorite nanocomposite hydrogel material.
[0044] Example 3: Preparation of double cross-linked lithium laponite composite hydrogel 3 Accurately weigh 0.15g Laponite and 5ml deionized water, add them to a beaker, and disperse them evenly by ultrasonication. Accurately weigh 0.3g of monomer methyl methacryloylethyl sulfobetaine (SBMA), add them to a beaker, and disperse them by ultrasonication to obtain a SBMA-hectorite composite.
[0045] SBMA-hectorite complex, 1.5g of acrylic acid (AA), 0.003g of crosslinker N,N-methylenebisacrylamide (MBA) and 0.0126g of initiator potassium persulfate (KPS) were added to 5ml of water and ultrasonicated again to ensure that all components were completely dissolved. Subsequently, 5 microliters of catalyst tetramethylethylenediamine (TEMED) were quickly added, and after being fully stirred, the mixture was immediately filled between two layers of polytetrafluoroethylene (PTFE)-covered glass slides with a thickness of about 1.5 mm, and placed in a drying oven at 80°C for crosslinking and curing for 0.5 h to prepare a double-crosslinked hectorite nanocomposite hydrogel material.
[0046] The morphology of the hydrogel in Example 3 was characterized by SEM. Figure 3 As shown. Compared with the morphology of Example 1 Figure 2 In comparison, with the increase of Laponite content, not only the pore size tends to decrease, but also the pore wall becomes thinner. This special porous structure is conducive to the uniform distribution of stress, effectively preventing the concentrated accumulation of stress at the weak points of the material, thereby inhibiting the initiation of microcracks and ensuring the excellent mechanical strength of the hydrogel. In addition, no significant particle agglomeration was observed in the cross-section SEM observation results, confirming the excellent dispersibility of Laponite nanoparticles in the composite hydrogel system.
[0047] Example 4: Preparation of double cross-linked hectorite composite hydrogel 4 Accurately weigh 0.20 g of Laponite and 5 ml of deionized water, add them to a beaker, and disperse them evenly by ultrasonication. Accurately weigh 0.3 g of monomer methyl methacryloylethyl sulfobetaine (SBMA), add them to a beaker, and disperse them by ultrasonication to obtain a SBMA-hectorite composite.
[0048] SBMA-hectorite complex, 1.5g of acrylic acid (AA), 0.003g of crosslinker N,N-methylenebisacrylamide (MBA) and 0.0126g of initiator potassium persulfate (KPS) were added to 5ml of water and ultrasonicated again to ensure that all components were completely dissolved. Subsequently, 5 microliters of catalyst tetramethylethylenediamine (TEMED) were quickly added, and after being fully stirred, the mixture was immediately filled between two layers of polytetrafluoroethylene (PTFE)-covered glass slides with a thickness of about 1.5 mm, and placed in a drying oven at 80°C for crosslinking and curing for 0.5 h, thereby preparing a double-crosslinked hectorite nanocomposite hydrogel material.
[0049] Example 5: Preparation of EGCG-Cu Nanocomplex 50 mg PVP was accurately weighed and dissolved in 10 mL deionized water, and then 17 mg CuCl2·2H2O was added for ultrasonic dispersion, and then 28.98 mg EGCG was added to react for 30 minutes, and then NaOH solution was added dropwise to the solution, while the pH value was measured using a pH meter until the desired pH value (7.2) was reached. After 3 hours of reaction, the final product was separated by centrifugation, washed three times with deionized water, and then freeze-dried to obtain the EGCG-Cu nanocomplex.
[0050] Example 6: Preparation of EGCG-Cu Nanocomplex 50 mg of PVP was accurately weighed and dissolved in 10 mL of deionized water, and then 21.82 mg of CuSO4·5H2O was added for ultrasonic dispersion, and then 30 mg of EGCG was added for 40 minutes, and then NaOH solution was added dropwise to the solution, while the pH value was measured using a pH meter until the desired pH value (7.5) was reached. After 3 hours of reaction, the final product was separated by centrifugation, washed three times with deionized water, and then freeze-dried to obtain EGCG-Cu nanocomplex.
[0051] Example 7: Preparation of hectorite composite antibacterial and antioxidant hydrogel 1 The double-crosslinked hectorite composite hydrogel sample prepared in Example 4 was freeze-dried and then immersed in 5 mL of a 0.5 mg / ml deionized water solution of the EGCG-Cu nanocomplex prepared in Example 5 for 24 h to obtain a hectorite nanocomposite hydrogel sample loaded with EGCG-Cu. The hydrogel was taken out with tweezers, the residual mixed solution on the surface was slowly rinsed, and the hydrogel was placed in a vacuum drying oven and dried at a constant temperature for two days.
[0052] The morphology of the hydrogel in Example 7 was characterized by SEM. Figure 4As shown, the EGCG-Cu nanoscale complex formed by EGCG and copper ions was successfully loaded onto the blank hydrogel of Example 4.
[0053] Example 8: Preparation of hectorite composite antibacterial and antioxidant hydrogel 2 The double-crosslinked hectorite composite hydrogel sample prepared in Example 3 was freeze-dried and then immersed in 5 mL of a 0.4 mg / ml deionized water solution of the EGCG-Cu nanocomplex prepared in Example 6 for 12 h to obtain a hectorite nanocomposite hydrogel sample loaded with EGCG-Cu. The hydrogel was taken out with tweezers, the residual mixed solution on the surface was slowly rinsed, and the hydrogel was placed in a vacuum drying oven and dried at a constant temperature for two days.
[0054] The adhesion properties of the hydrogel system of Example 8 on the skin surface were tested. The experimental results are as follows: Figure 5 As shown. Tests have found that the hydrogel system can exhibit excellent adhesion properties on the skin surface and maintain stable adhesion even during wrist joint movement. The addition of laponite and zwitterions allows the nanocomposite hydrogel to carry both cationic quaternary ammonium salt groups and anionic sulfonate groups, strengthening the mutual attraction with the charge or polar groups on the target surface, thereby significantly improving the adhesion efficiency.
[0055] Comparative Example 1: Preparation of hectorite composite antibacterial hydrogel Accurately weigh 0.2182 g of CuCl2·2H2O and dissolve it in 10 ml of deionized water. Soak a certain mass of freeze-dried double-crosslinked hectorite composite hydrogel sample in 5 mL of the prepared mixed solution for 24 h to obtain a hectorite composite antibacterial hydrogel sample loaded with copper ions. Take out the hydrogel with tweezers, slowly rinse the residual mixed solution on the surface, and put it in a vacuum drying oven for constant temperature drying for two days.
[0056] Comparative Example 2: Preparation of Hectorite Composite Antioxidant Hydrogel Accurately weigh 0.2 g of EGCG and dissolve it in 10 ml of deionized water. Soak a certain mass of freeze-dried double-crosslinked hectorite composite hydrogel sample in 5 mL of the prepared mixed solution for 24 h to obtain the hectorite composite antioxidant hydrogel sample loaded with EGCG. Take out the hydrogel with tweezers, slowly rinse the residual mixed solution on the surface, and put it in a vacuum drying oven to dry at a constant temperature for two days.
[0057] Performance Characterization 1: Mechanical Properties like Figure 6As shown, the prepared hydrogel of Example 4 exhibits excellent deformation ability, and can not only easily withstand external forces such as stretching, bending and compression, but also achieve knotting without breaking. The hydrogel can be easily stretched, bent, compressed and knotted. This shows that the hydrogel has excellent flexibility, excellent durability and good tensile properties.
[0058] Tensile tests were performed on the double cross-linked lithium laponite composite hydrogel samples of Example 1, Example 2, Example 3, and Example 4. The Laponite contents in Example 1, Example 2, Example 3, and Example 4 were 0.05, 0.10, 0.15, and 0.20 g, respectively. Figure 7 As shown in the figure, with the increase of Laponite content, the strength of the hydrogel is significantly enhanced, and its tensile strength and toughness are significantly increased, among which the maximum elongation at break of the hydrogel in Example 4 reaches 1640%. This improvement is mainly due to the effective enhancement of the crosslinking density of the hydrogel network by Laponite as an inorganic crosslinking agent. Its unique layered structure not only enhances the interaction between the polymer chain and the nanoparticles, but also effectively inhibits the further expansion of the cracks.
[0059] Performance Characterization 2: Drug Release At room temperature, three portions of the hydrogel prepared in Example 7 with a mass of 10 mg were cut and placed in centrifuge tubes containing 10 mL of PBS buffer solution with pH values of 6.5, 7.4 and 8.5, respectively, to carry out in vitro release experiments of EGCG under different pH conditions. The experimental environment temperature was maintained at (37 ± 0.5) ° C, and the oscillation frequency was 20 r / min. In this system, 3 mL of PBS buffer was sampled from the centrifuge tube of each pH group at every predetermined time point, and 3 mL of the corresponding PBS buffer was supplemented to keep the total volume consistent with the initial conditions. The absorbance of EGCG was measured at the characteristic absorption peak of 279 nm using a UV-visible spectrometer. The EGCG release concentration was calculated by the standard curve at the corresponding pH, and the cumulative release rate of EGCG was calculated to obtain the in vitro release curve of EGCG at different pH.
[0060] Taking the in vitro cumulative release curve of EGCG in the hydrogel of Example 7 as an example, Figure 8As shown in the figure, EGCG is relatively stable at a pH of 6.5, with a release rate of 32.8%. At a pH of 7.4, the stability of EGCG weakened, with a release rate of 62.85%. When the pH value was 8.5, the release rate of EGCG was the highest, reaching 82.35%. In the development process of chronic wound infection, the pH of the wound microenvironment tends to be alkaline, and the bacterial load and reactive oxygen species (ROS) levels increase significantly. Under this alkaline condition, EGCG exhibits enhanced release characteristics, responding in time and meeting the high demand of the infected wound area to resist microbial invasion and oxidative stress. In addition, the regulated low-amount release of EGCG in a near-neutral or acidic pH environment helps to maintain the homeostasis of the wound microenvironment, thereby intervening and inhibiting the process of the wound evolving into a chronic state, reflecting its flexible regulation of release under different pH environments.
[0061] Performance Characterization 3: Antibacterial Test In the antibacterial test, the main instruments and equipment such as high-temperature and high-pressure steam autoclave, clean workbench, constant temperature oscillator and analytical electronic balance were used, as well as LB broth medium and agar powder as the main reagents for the preparation of the culture medium. At the same time, Staphylococcus aureus was used as the test strain to test the antibacterial properties of the samples to be tested. Luria-Bertani (LB) liquid culture medium and LB solid culture medium were prepared according to the standard process. After ensuring sterile conditions, the bacterial suspension of Staphylococcus aureus was prepared. Single colonies were picked and added to the liquid culture medium, and then shaken and cultured overnight (15 h) in a constant temperature oscillator (37°C, 200 rpm). At the same time, the samples to be tested were sterilized by ultraviolet light to ensure the accuracy of the experiment. In the experiment, the Staphylococcus aureus suspension was first diluted to 10 with PBS buffer. 6 The appropriate concentration of CFU / mL was then evenly coated on the surface of LB solid culture medium. The sample was attached to the culture medium. After the culture was completed, the culture dish was photographed and the diameter of the inhibition zone was measured.
[0062] like Fig. 9 By comparing the sizes of inhibition zones between different treatment groups, it was found that all test samples showed antibacterial activity against Staphylococcus aureus, among which the size of the inhibition zone of the blank hydrogel group in Example 4 was about 3 mm, which may be due to the fact that SBMA and Laponite themselves have certain antibacterial properties. The size of the inhibition zone of the EGCG-loaded group in Comparative Example 2 was about 6 mm, which shows that the addition of EGCG optimizes its antibacterial properties. The sample loaded with EGCG-Cu in Example 7 showed the largest inhibition zone diameter of 28 mm, so it was concluded that the lithium soapstone nanocomposite hydrogel loaded with EGCG-Cu is an ideal material for medical dressings.
[0063] Performance Characterization 4: Antioxidant Test Weigh 10 mg DPPH and dissolve it in 50 mL ethanol to obtain DPPH mother solution. Take 20 mL of the mother solution and dilute it with 80 mL ethanol to obtain a DPPH solution with a concentration of 40 µg / mL. The absorbance of the DPPH solution was measured using a UV-visible spectrometer, and then the hydrogel was placed in the DPPH solution. The absorbance of the solution at 517 nm was continuously monitored and recorded by a UV-spectrophotometer. The scavenging efficiency of the hydrogel on free radicals was calculated based on the ratio of the final absorbance to the initial absorbance at 517 nm. The results are shown in Fig.10 .
[0064] like Fig.10 Figure a shows that after adding the hydrogel of Example 7, the absorption peak intensity at a wavelength of 517 nm decreases significantly. Figures c and d show the photos of the DPPH solution without adding the hydrogel and 60 minutes after adding the hydrogel, respectively. The solution changes from the initial purple to yellow, indicating that the free radicals are effectively scavenged. Figure b shows the calculated final scavenging ratio of Comparative Example 1 and Example 7 for DPPH free radicals. It can be found that the hydrogel of Comparative Example 1 without EGCG loading does not have a significant free radical scavenging effect, and the free radical scavenging effect of Example 7 loaded with EGCG can reach up to more than 80%.
[0065] The present invention provides a hectorite composite antibacterial and antioxidant hydrogel and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a hectorite composite antibacterial and antioxidant hydrogel, characterized in that: The steps include: (1) Preparation of zwitterionic monomer-hectorite composite The hectorite is dispersed in deionized water to obtain a dispersion, and a zwitterionic monomer is added and adsorbed on the surface of the hectorite through an interionic action to obtain a zwitterionic monomer-hectorite composite; (2) Preparation of double-crosslinked lithium soapstone composite hydrogel Adding zwitterionic monomer-hectorite complex, main monomer, crosslinking agent, initiator and catalyst into water, stirring fully to obtain precursor solution, and after crosslinking and curing, obtaining double crosslinked hectorite composite hydrogel; (3) Preparation of EGCG-Cu nanocomplex A functional polymer deionized water solution was prepared, an inorganic copper salt was added for ultrasonic dispersion, EGCG was added for reaction, the final product was separated by centrifugation, and the product was washed and freeze-dried to obtain an EGCG-Cu nanocomplex; (4) Preparation of hectorite composite antibacterial and antioxidant hydrogel The double-crosslinked lithium soapstone composite hydrogel in step (2) is immersed in the deionized water solution of the EGCG-Cu nanocomplex prepared in step (3) to allow the hydrogel layer to fully swell, and then taken out and vacuum dried to obtain the hydrogel.
2. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 1, characterized in that: In step (1), the zwitterionic monomer is any one of carboxylic acid betaine methyl methacrylate, 2-methacryloyloxyethyl phosphorylcholine, polycarboxylic acid betaine, and methacryloylethyl sulfonyl betaine; the hectorite is nanoclay sodium magnesium lithium silicate, and its mass percentage in the dispersion is 0.2~8%; the molar ratio of the nanoclay sodium magnesium lithium silicate to the zwitterionic monomer is 1:0.2~1:
10.
3. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 1, characterized in that: In step (2), the main monomer is acrylic acid or methacrylic acid; The crosslinking agent includes any one of NN methylenebisacrylamide, divinylbenzene, N,N-bis(acryloyl)cystamine, ethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, and 2,2-dithiodiethanol diacrylate; The initiator is a thermal initiator, a peroxide initiator or an azo compound initiator; wherein the thermal initiator includes any one of azobisisopropionitrile, azobisisobutyronitrile, azobisisoheptylnitrile and dibenzoyl peroxide, and the peroxide initiator includes any one of hydrogen peroxide, ammonium persulfate or potassium persulfate; The catalyst is tetramethylethylenediamine.
4. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 3, characterized in that: In step (2), the concentration of the main monomer in the precursor solution is 0.05-1 g / mL, the mass of the zwitterionic monomer accounts for 1-40% of the mass of the main monomer, the cross-linking agent accounts for 0.05-1% of the mass of the main monomer, the initiator accounts for 0.05-2% of the mass of the main monomer, and the catalyst accounts for 0.05-2% of the mass of the main monomer.
5. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 1, characterized in that: In step (2), the precursor solution is filled between two layers of polytetrafluoroethylene-coated glass slides with a thickness of about 1 to 2 mm, and placed in a drying oven at 60 to 120° C. for cross-linking and curing for 30 to 240 minutes to obtain a double-cross-linked lithium soapstone composite hydrogel.
6. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 1, characterized in that: In step (3), the functional polymer is polyvinyl pyrrolidone, the concentration of the prepared aqueous solution is 10-100 mg / mL, the inorganic copper salt is any one of CuCl2, Cu(NO3)2, and CuSO4; the molar ratio of EGCG to the inorganic copper salt is between 1:1 and 1:3, and the mass of the functional polymer is 50-200% of the total mass of EGCG and the inorganic copper salt.
7. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 3, characterized in that: In step (3), the functional polymer, inorganic copper salt and EGCG are mixed and the pH value is adjusted to 7-8. After reacting for 1-6 hours, the final product is separated by centrifugation, washed three times with deionized water, and freeze-dried to obtain the EGCG-Cu nanocomplex.
8. The method for preparing the hectorite composite antibacterial and antioxidant hydrogel according to claim 3, characterized in that: In step (4), the concentration of the prepared deionized water solution of EGCG-Cu nanocomplex is 0.1-2 mg / mL; the double-crosslinked hectorite composite hydrogel is immersed in the deionized water solution of EGCG-Cu nanocomplex for 6-24 hours, and then the residual mixed solution on the surface is taken out and rinsed.
9. The hectorite composite antibacterial and antioxidant hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the hectorite composite antibacterial and antioxidant hydrogel according to claim 9 in the preparation of wound dressings.
Citation Information
Cited By
Preparation method of hectorite-based nano composite antibacterial material
CN122162810A